Caudilhismo, território e relações sociais de poder: o caso de Aparício Saraiva na região fronteiriça entre Brasil e Uruguai (1896-1904) - Dobke, Pablo Rodrigues (2015)
The Master's thesis, developed in the Research Line "Integration, Politic and Border" of the Post Graduate program in History at the Federal University of Santa Maria, aims at investigating the role of the uruguayan border caudilho Aparicio Saraiva the century purposes nineteenth and early twentieth considering its social relations in the materialization of a territorial power and territorial of that power. In this sense, the border, the individual, the party and society, print a symbolic capital that characterizes the caudilhismo of the late nineteenth and early twentieth centuries. From a bibliographical and documentary research seek the perspective of political history working with the social and power relations taking in the historical works of the period as in later, in the analysis of documentation (consisting of diaries, letters and journals) the arguments of this research. This research was help FAPERGS/CAPES.